Radon concentration measurement and effective dose assessment in drinking groundwater for the adult population in the surrounding area of a thermal power plant. (8th March 2022) - Kumar, Mukesh; Kumar, Pankaj; Agrawal, Anshu; Sahoo, B. K.
Abstract: Radon in the household water collected from hand pumps is measured using a continuous radon monitor. Water samples are collected from 25 villages from the surrounding regions of the National Capital Power Cooperation (NTPC), Dadri. The radon concentration ranges from 17±1 to 68±3 Bql −1 with a mean value of 33±13 Bql −1 . The measured radon concentration in all collected samples lies well within the limit of 100 Bql −1 as set by the World Health Organization (WHO). The mean values of the annual effective dose due to ingestion of radon and due to the inhalation of radon released from water are 84±33 and 167±65 μSvy −1, respectively. In addition, the mean values of estimated total annual effective doses are found to be 167±65 μSvy −1 . The mean value of total annual effective doses is found to be higher than the reference dose level of 100 μSvy −1 recommended by the WHO and the United Nations Scientific Committee on the Effect of Atomic Radiation (UNSCEAR). The mean values of effective doses per annum to the lungs and stomach are 9.9±3.9 and 10.1±3.9 μSv, respectively. HIGHLIGHTS: SMART Rn Duo: A Continuous radon monitor. Radon concentration present in the drinking groundwater is measured. The annual effective ingestion, inhalation, and total dose of radon are measured. Radon concentration is found to be below the recommended action level of 100 Bql −1 proposed by the EU and WHO. The mean value of total annual effective dose is found to be higher compared to the safe limit recommended by the WHO. Graphical Abstract